Clinical and Laboratory Predictors of COVID-19-Related In-hospital Mortality; a Cross-sectional Study of 1000 Cases - Mohammadi , Zohreh; Faghih Dinevari, Masood; Vahed, Nafiseh; Ebrahimi Bakhtavar, Haniyeh; Rahmani, Farzad (Archives of Academic Emergency Medicine, 2022)
Introduction: Identifying patients at risk for mortality and using appropriate treatment for each patient based on their situation could be an effective strategy in improving their outcome. This study aimed to evaluated the predictors of COVID-19 in-hospital mortality. Methods: This descriptive cross-sectional study was conducted on all adult COVID-19 patients who were managed in Imam-Reza and Sina Hospitals, Tabriz, Iran, from November 2020 until December 2021. The demographic, clinical, and laboratory characteristics of patients were evaluated and predictors of in-hospital mortality were identified using logistic regression model. Results: 1000 patients with the mean age of 56.34 ± 18.00 years were studied (65.7% male). There were significant associations between COVID-19 in-hospital mortality and hospitalization above five days (p = 0.001), white blood cell count (WBC) > 4000 Cells*103/mL (p < 0.01), aspartate aminotransferase (AST) above 40 IU/L (p = 0.001), alanine transaminase (ALT) above 40 IU/L (p = 0.001), creatinine above 1.4 mg/dL (p = 0.007), urea above 100 mg/dL (p = 0.024), and SaO2 below 80% (p = 0.001). Hospital stay above five days (OR: 3.473; 95%CI: 1.272 - 9.479; p = 0.15), AST above 40 IU/L (OR: 0.269, 95%CI: 0.179 - 0.402; p = 0.001), creatinine above 1.4 mg/dL (OR: 0.529; 95%CI: 0.344 - 0.813; p = 0.004), urea above 100 mg/dL (OR: 0.327, 95%CI: 0.189 - 0.567; p = 0.001), and SaO2 below 80% (OR: 8.754, 95%CI: 5.413 - 14.156; p = 0.001) were among the independent predictors of COVID-19 in-hospital mortality. Conclusion: The mortality rate of patients with COVID-19 in our study was 29.9%. Hospitalization of more than five days, AST above 40 IU/L, creatinine above 1.4 mg/dL, urea above 100 mg/dL and SaO2 < 80% were independent risk factors of in-hospital mortality among patients with COVID-19.